Some estimations of Zagreb indices - Liu, Bolian (Utilitas Mathematica, 2007)
For a (molecular) graph G, the first Zagreb indices M1 is equal to the sum of the squares of the degrees of the vertices, and the second Zagreb index M2 is equal to the sum of the products of the degrees of pairs of adjacent vertices. We give some new bounds for Zagreb indices and provide a matrix-representation and its applications.